Upaya Pelayanan Gereja yang Relevan pada Masa Pasca Pandemi COVID 19 - Paipen Wonda (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2023)
The Covid 19 pandemic has gradually experienced positive changes. In several places, they have adapted to a new lifestyle called the new normal era. However, the Covid-19 pandemic still leaves problems for the church. A lot of research has been produced by academics and researchers on how to build the concept of Christian service during the Covid-19 pandemic. Most of the research presents the effectiveness of services through online media. However, the research that has been made has not been able to identify potential problems with internet-based service systems. Mental health issues, apathy towards the church, and changes in religiosity could not be detected in this study. This paper contains an analysis of potential problems in church services in the post-Covid 19 pandemic. Through a literature analysis approach, this research presents the strategies needed by churches in determining relevant services. In addition, this study also conducts a historiographical analysis of the development of church ministry according to Acts 1-6. The purpose of this research is to find formulations of efforts that are relevant for the church in carrying out services in the post-pandemic Covid 19. As a result, the church must rebuild damaged spirituality and pay intensive attention to the congregation to restore enthusiasm for serving God.Pandemi Covid 19 telah berangsur-angsur mengalami perubahan positif. Di beberapa tempat telah beradaptasi dengan pola hidup baru yang disebut era new normal. Namun, pandemi Covid-19 masih menyisakan masalah bagi gereja. Telah banyak penelitian yang dihasilkan oleh para akademisi dan peneliti tentang bagaimana membangun konsep pelayanan Kristen pada masa pandemic Covid-19. Sebagaian besar penelitian menyuguhkan efektifitas pelayanan melalui media online. Namun, penelitian yang telah dibuat belum mampu mengidentifkasi potensi masalah dari sistem pelayanan berbasis internet. Isu kesehatan mental, apatisme terhadap gereja serta perubahan religiusitas tidak mampu dideteksi pada penelitian tersebut. Tulisan ini berisi pemaparan analisis potensi masalah dalam pelayanan gereja pada masa pasca pandemi Covid 19. Melalui pendekatan analisis pustaka, penelitian ini menyuguhkan strategi yang diperlukan gereja dalam menetapkan pelayanan yang relevan. Selain itu, penelitian ini juga melakukan analisis historiografi terhadap perkembangan pelayanan gereja menurut Kisah Para Rasul 1-6. Tujuan penelitian ini adalah untuk menemukan rumusan upaya yang relevan bagi gereja dalam melakukan pelayanan pada pasca pandemic Covid 19. Hasilnya, gereja harus membangun kembali kerohanian yang rusak dan memberikan perhatian yang intensif kepada jemaat untuk mengembalikan kegairahan dalam melayani Tuhan.